The Correlation Between Reading Comprehension and Vocabulary Mastery of Class XI Students at Madrasah Aliyah Al-Khairaat Ulatan - Fahrani, Fahrani; Afifah, Afifah; Zuhra, Zuhra; Suleman, Suleman (Datokarama English Education Journal, 2023)
This study aims to investigate the relationship between the reading comprehension and vocabulary proficiency of students in the eleventh grade at Madrasah Aliyah Al-khairaat Ulatan. The research employs a quantitative approach with a correlational design, and the sampling method utilized is total sampling. The study includes 26 students from the eleventh-grade class at Madrasah Aliyah Al-khairaat Ulatan. The research instrument consists of a multiple-choice test, and data collection involves two types of tests: a reading comprehension test and a vocabulary mastery test, each comprising 10 questions. Data analysis was conducted manually using SPSS 25. The findings of the research reveal a significant correlation between reading comprehension and vocabulary mastery, with a two-tailed significance (Sig.) value of 0.007. The calculated correlation coefficient (r) is 0.518, indicating a strong correlation (greater than 0.5 but less than 0.75). The Pearson correlation coefficient of 1 signifies a positive correlation between the two variables. Therefore, the research concludes that the alternative hypothesis (Ha): "The value of r count 0.518 > r table 0.388" is accepted, indicating a correlation between reading comprehension and vocabulary mastery among students in class XI at Madrasah Aliyah Al-khairaat Ulatan.